Perbedaan Pendekatan Konstruktivis Dan Pendekatan Matematika Realistik Terhadap Kemampuan Berpikir Logis Siswa Smp Muhammadiyah 01 Medan - Lairani Dwi Alvira (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The purpose of this study is to determine whether there are differences between the Constructivist Approach and the Realistic Mathematics Approach to the  ability to think logically in students of Muhammadiyah 01 Medan junior high school. The population in this study were all 7th grade students of Muhammadiyah 01 Medan junior high school, while the sample was 7th grade T3 totaling 35 students as experimental class I and 7th grade T4 totaling 35 students as experimental class II. The sampling technique used is Simple Random Sampling. This type of research is quasi-experimental. From the results of research that has been done, the average value of pretest in experimental class I is 47.86 and the average posttest score is 83.57, it shows that students' logical thinking ability is better after applying constructivist approach during the learning process.  While  the  experimental  class  II  obtained  an  average  pretest  score of 46.86 and an average posttest of 78.71 it shows that students' logical thinking abilities are better after applying a realistic mathematical approach during the learning process. Then the t test was conducted using an independent sample t-test to find out whether there were differences between the two approaches used in this study and a tcount of 1.6526 and a ttable = 1.995 was obtained. Based on the two-party testing criteria,  the  tcount is located  between  -1.995  and  1.995 (-1.995 <1.6526 <1.995), then H0 is accepted and Ha is rejected, meaning it can be concluded that there is no difference between the constructivist approach and the realistic mathematical approach to students' logical thinking abilities in learning mathematics set material in SMP Muhammadiyah 01 Medan.